Functionalization of single-walled carbon nanotubes and their binding to cancer cells - Madani SY (Dove Medical Press, 2012)
Seyed Yazdan Madani1, Aaron Tan1, Miriam Dwek2, Alexander M Seifalian1,31UCL Centre for Nanotechnology and Regenerative Medicine, University College London, London, UK; 2Department of Molecular and Applied Biosciences, School of Life Sciences, University of Westminster, London, UK; 3Royal Free Hampstead NHS Trust Hospital, London, UKBackground: Single-walled carbon nanotubes (SWCNTs) have novel properties including their nanoscale size and ease of cellular uptake. This makes them useful for drug delivery, and their photo-thermal effects make them potentially useful in a wide range of applications, particularly the treatment of solid tumors. The poor solubility of SWCNTs has, however, been an issue that may potentially limit the utility of SWCNTs for cancer treatment. Functionalization of the surface of the tubes may be an approach to overcome this problem.Methods: SWCNTs were refluxed in HNO3/H2SO4 (1:3) at 120°C for 120 minutes. Transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FTIR), contact angle measurements, and near infrared (NIR) light exposure were used to assess the functionalization process. The attachment of a carbohydrate-binding protein (lectin) labeled with fluorescein isothiocyanate to the functionalized SWCNTs enabled evaluation of the functionalization step via confocal microscopy. The lectin from Helix pomatia, (Helix pomatia agglutinin [HPA]), can detect changes in protein glycosylation associated with aggressive metastatic cancer. The interaction between the lectin HPA alone and HPA conjugated to the functionalized SWCNTs with human breast cancer cells (MCF-7) was measured using a quartz crystal microbalance biosensor.Results: Following the functionalization process, TEM images showed a layer had formed on the surface of the SWCNTs. In the FTIR experiment, results illustrated the presence of the –COOH group on the functionalized SWCNTs. Contact angle measurements showed that upon functionalization the hydrophilicity of the SWCNTs increased. The temperature increase in the liquid (supernatant) surrounding the functionalized SWCNTs following exposure to light in the NIR (808 nm) was greater than for non-functionalized SWCNTs. The biosensor work showed that HPA binds with high affinity (nanomolar range) to human breast cancer cells; HPA-binding properties to MCF-7 cells were retained following conjugation to the functionalized SWCNTs.Conclusion: Treating pure SWCNTs with HNO3/H2SO4 (1:3) at 120°C for 120 minutes is an effective method for functionalization of SWCNTs. HPA linked to SWCNTs is a suitable candidate for the delivery of the functionalized SWCNTs to cancer cells.Keywords: SWCNT, HPA lectin, human breast cancer cells